1987
DOI: 10.1210/endo-121-1-98
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Thyrotropin-Releasing Hormone Prohormone Messenger Ribonucleic Acid in Rat Brain by in Situ Hybridization*

Abstract: We studied the distribution of pro- TRH mRNA in rat brain by in situ hybridization histochemistry using radiolabeled single stranded cRNA probes to confirm the hypothesis that the TRH precursor is distributed beyond regions that contain immunoreactive TRH. All regions of the central nervous system previously recognized to contain TRH showed hybridization. Hypophysiotropic neurons in the medial parvocellular division of the paraventricular nucleus showed more intense hybridization than anterior parvocellular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
81
2

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(103 citation statements)
references
References 28 publications
20
81
2
Order By: Relevance
“…7). These results correlate with the distribution of preproTRH mRNA in the mammalian hypothalamic region (Segerson et al 1987, Guldenaar et al 1996, Fliers et al 1998. In addition, these researchers found a small number of preproTRH mRNAcontaining cells in the human and rat suprachiasmatic nucleus (SCN).…”
Section: In Situ Hybridizationsupporting
confidence: 57%
See 2 more Smart Citations
“…7). These results correlate with the distribution of preproTRH mRNA in the mammalian hypothalamic region (Segerson et al 1987, Guldenaar et al 1996, Fliers et al 1998. In addition, these researchers found a small number of preproTRH mRNAcontaining cells in the human and rat suprachiasmatic nucleus (SCN).…”
Section: In Situ Hybridizationsupporting
confidence: 57%
“…Results of immunocytochemical studies in hypothyroid rats suggested that only the TRH cells in the parvocellular portion of the PVN are involved in the regulation of the hypothalamic-pituitary-thyroid (HPT) axis (Nishiyama et al 1985). Data on the distribution of the preproTRH mRNA-containing cells in the human and rat hypothalamus generally agreed with immunocytochemical data (Segerson et al 1987, Guldenaar et al 1996, Fliers et al 1998. The distribution of TRH peptide in the chicken brain has also been studied in detail via immunocytochemistry (Józsa et al 1988) and radioimmunoassays (Geris et al 1999).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The neuropeptide thyrotropin-releasing hormone (TRH), first discovered as a hypophysiotropic hormone (Boler et al, 1969;Burgus et al, 1969), is strongly expressed in the nRt (Lechan et al, 1986;Segerson et al, 1987;Burgunder et al, 1999;Heuer et al, 2000). Furthermore, prominent TRH receptor (TRHR) expression occurs in thalamic relay nuclei (Cao et al, 1998;Heuer et al, 2000;O'Dowd et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the rat brain, pro-TRH-ir cells were more widely distributed than TRHir cells, suggesting that TRH prohormone may be differentially processed in certain regions of the brain. In situ hybridization (ISH) of mRNAs for TRH precursor and also prohormone convertase (PC) demonstrated that PC genes were coexpressed in a subset of pro-TRH-expressing neurons in the rat (Segerson et al, 1987;Pu et al, 1996) and frog (Pu et al, 1995).…”
Section: Introductionmentioning
confidence: 99%